2014
DOI: 10.1002/anie.201408760
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free σ‐Bond Metathesis in 1,3,2‐Diazaphospholene‐Catalyzed Hydroboration of Carbonyl Compounds

Abstract: The first metal-free catalytic hydroboration of carbonyl derivatives has been developed in which a catalytic amount of 1,3,2-diazaphospholene effectively promotes a hydroboration reaction of aliphatic and aromatic aldehydes and ketones. The reaction mechanism involves the cleavage of both the PO bond of the alkoxyphosphine intermediate and the BH bond of pinacolborane as well as the formation of PH and BO bonds. Thus, the reaction proceeds through a non-metal σ-bond metathesis. Kinetic and computational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(122 citation statements)
references
References 68 publications
(12 reference statements)
10
112
0
Order By: Relevance
“…The reaction mixture was allowed to stir for 10 min at which time a0 .2 mL aliquot was taken from the reaction mixture and the volatiles were removed under vacuum. Data for (4-ClC 6 H 4 ) 2 CHOBPin [20] and MesCH 2 OBPin [38] were consistent with the literature. In as imilar manner,t he reaction was conducted with a1mol %loading of [IPr·Cd(OTf) 2 ] 2 (0.008 g, 0.005 mmol), benzophenone (0.092 g, 0.51 mmol), HBPin (73 mL, 0.51 mmol) in 2mL of THF.T he reaction was also conducted with a0 .1 mol %l oading of [IPr·Cd(OTf) 2 ] 2 (0.006 g, 0.004 mmol), benzophenone (0.681 g, 3.74 mmol), HBPin (542 mL, 3.74 mmol) and 5mLo fT HF.R elevant data are presented in Table 1.…”
Section: Catalytic Hydrosilylation Of Benzophenonesupporting
confidence: 87%
See 1 more Smart Citation
“…The reaction mixture was allowed to stir for 10 min at which time a0 .2 mL aliquot was taken from the reaction mixture and the volatiles were removed under vacuum. Data for (4-ClC 6 H 4 ) 2 CHOBPin [20] and MesCH 2 OBPin [38] were consistent with the literature. In as imilar manner,t he reaction was conducted with a1mol %loading of [IPr·Cd(OTf) 2 ] 2 (0.008 g, 0.005 mmol), benzophenone (0.092 g, 0.51 mmol), HBPin (73 mL, 0.51 mmol) in 2mL of THF.T he reaction was also conducted with a0 .1 mol %l oading of [IPr·Cd(OTf) 2 ] 2 (0.006 g, 0.004 mmol), benzophenone (0.681 g, 3.74 mmol), HBPin (542 mL, 3.74 mmol) and 5mLo fT HF.R elevant data are presented in Table 1.…”
Section: Catalytic Hydrosilylation Of Benzophenonesupporting
confidence: 87%
“…The resulting catalytic hydroborylationr eactionw as found to be much more rapid than hydrosilylation, with the reaction going to 98 % completion after 10 min in the presenceo fa1mol %l oading of 2 (TOF = 593 h À1 ). [20] High turnover frequencies were also maintained with more sterically hindereds ubstrates. [19] and ar ecently reported diazaphospholene catalyst prepared by Kinjo and co-workers (TOF = 1.8 h À1 at 90 8C).…”
Section: Resultsmentioning
confidence: 96%
“…Gudat and co-workers seminal work demonstrated that 1a is af orm of super-hydride, [3] yet with common features of organic reagents, [4] such as relatively low cost and good solubility in organic media. Consequently,an umber of N-heterocyclic phosphorus hydrides ( Figure 1) and their analogues have been developed in recent years,rendering many originally infeasible reactions to occur under metal-free conditions,s uch as reductions of polar olefins, [5] imines, [5a] ketones, [6] and azo compounds, [7] valorization of CO 2 , [8] and hydroboration of pyridines. Consequently,an umber of N-heterocyclic phosphorus hydrides ( Figure 1) and their analogues have been developed in recent years,rendering many originally infeasible reactions to occur under metal-free conditions,s uch as reductions of polar olefins, [5] imines, [5a] ketones, [6] and azo compounds, [7] valorization of CO 2 , [8] and hydroboration of pyridines.…”
Section: Contrastingwiththewell-knownproticreactivityofconven-mentioning
confidence: 99%
“…The difference in substrate polarization could be expected to invert the sense of E–H addition to 1 , with hydride translocating to the phosphorus center and the attendant E + fragment migrating to ligand nitrogen. This mode of activation would result in formation of a P -hydrido-1,3,2-diazaphospholene ( C ), a class of compound that Gudat 18 has shown to exhibit significant hydridic reactivity and that Kinjo 19 and most recently Speed 20 have capitalized on in catalysis. We wished to ascertain whether interfacing these elementary reactivities with a subsequent group transfer from the pendant N -methylanilide with regeneration of 1 would permit an overall catalytic E–H transfer via a new P–N cooperative scheme.…”
Section: Introductionmentioning
confidence: 99%